FROST INVESTIGATION 1944. REPORT ON FROST INVESTIGATIONS AND PAVEMENT BEHAVIOR TESTS DOW FIELD, BANGOR, MAINE. - ARCTIC CONSTRUCTION AND FROST EFFECTS LAB BOSTON MASS (1946)
This is a report of the frost investigations performed at Dow Field, Bangor, Maine, during the winter, spring and summer of 1944 by the Boston District Office. The purpose of these investigations was to determine the influence of frost action in the subgrade soils beneath both rigid and flexible pavements at Dow Field upon the gross plane weight evaluation of these pavements. (Author)